Maternal Characteristics and Malaria Prevalence among Children in Ghana - Ahiati, R. (University of Ghana, 2015)
Malaria threatens the lives of billions of people globally and leads to over one million deaths annually (WHO 2010). More than 90 per cent of the clinical cases and deaths in sub-Saharan Africa are caused by malaria (WHO 2011). Malaria kills an estimated one million children under five years of age per year or one child in every 30 seconds. Malaria is hyper-endemic in Ghana, accounting for 44% of outpatient attendance, 13% of all hospital deaths, and 22% of mortality among children less than five years of age. The study examined the maternal characteristics that influence the prevalence of malaria among children less than five years in Ghana, using a binary logistic regression model. Data for the study was obtained from 2008 Ghana Demographic and Health Survey (GDHS). The results showed that maternal characteristics such as, education, region of residence and religion were important predictors of malaria prevalence among children less than five years. However, it was found that the maternal characteristics such as; age, type of place of residence (rural and urban), ethnicity, marital status and wealth quintile were not good predictors of malaria prevalence. It was recommended, among other things that Government should also use religious leaders in scaling up the campaign to prevent and treat malaria. That is the communication and awareness committee of ministry of health and roll back malaria initiative programme in the country should see the importance of integrating religious gatekeepers in order to provide awareness about the position of religion on any policy or program to be implemented
Thesis (MA)- University of Ghana, 2015